2015
DOI: 10.1007/s10640-015-9930-0
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Influence of Substitute Sites in Nature Valuation by Using Spatial Discounting Factors

Abstract: This paper investigates the effect of nearby nature substitute sites on preferences for nature restoration. Contrary to prior studies, we use a respondent-centric approach to control for substitute sites. We assess each respondent-specific spatial context by computing densities of nature substitute sites within various ranges from each respondent's home. This approach considers the use and non-use values of nature together. Data from three similar discrete choice experiments carried out in Flanders (Belgium) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Sutherland and Walsh 1985;Bateman et al 2000Bateman et al , 2006 and is influenced by the availability and proximity of substitutes (e.g. De Valck et al 2017). Substitutes are increasingly incorporated in CE studies-either explicitly in the study design or implicitly in the data analysis-and were shown to impact preferences for environmental changes with significant implications for value aggregation Jørgensen et al 2013;Lizin et al 2016;De Valck et al 2017).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sutherland and Walsh 1985;Bateman et al 2000Bateman et al , 2006 and is influenced by the availability and proximity of substitutes (e.g. De Valck et al 2017). Substitutes are increasingly incorporated in CE studies-either explicitly in the study design or implicitly in the data analysis-and were shown to impact preferences for environmental changes with significant implications for value aggregation Jørgensen et al 2013;Lizin et al 2016;De Valck et al 2017).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…De Valck et al 2017). Substitutes are increasingly incorporated in CE studies-either explicitly in the study design or implicitly in the data analysis-and were shown to impact preferences for environmental changes with significant implications for value aggregation Jørgensen et al 2013;Lizin et al 2016;De Valck et al 2017). Distance decay has been also shown to be influenced by perceptions and characteristics of the good being valued (Andrews et al 2017).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…AREA) should be taken with caution, and we should be wary of claiming the clear superiority of this spatial discounting factor over the others. In any case, these results suggest a less pronounced discounting effect than that found by De Valck et al (2017), who report the use of the inverse of the squared distance as showing the best results. Very probably, the different characteristics of the case studies (an agricultural system in our case and the restoration of different natural sites in theirs, and the geographic context -Flanders/Andalusia, etc.)…”
Section: Alternative Approaches For Spatial Analysismentioning
confidence: 37%
“…As shown in Section 2.2, the distance to environmental sites may not be a sufficiently accurate measure for explaining the heterogeneity in individuals' WTP for scattered ecosystems (as most agricultural systems are). This explains why area-and density-based approaches have been proposed for these cases as alternative approaches for spatial discounting (Yao et al, 2014;Nielsen, Lundhede and Jacobsen, 2016;De Valck et al, 2017;Holland and Johnston, 2017). However, to the authors' knowledge, none of the previous works have explicitly explained the theoretical basis justifying the use of these spatial indexes.…”
Section: Methodological Proposal For Spatial Analysis In Sparsely-locmentioning
confidence: 99%
See 1 more Smart Citation